Burger bun with a mocaf flour (modified cassava flour) substitution and puree bit (Beta vulgaris L) as a source of dietary fiber: Roti burger dengan substitusi tepung mocaf (modified cassava flour) dan penambahan puree bit (Beta vulgaris L) sebagai sumber serat - Elysa Dwi Annganing; Yannie Asrie Widanti; Vivi Nuraini (Agrobiotek, 2025)
Bread is a food product made from wheat flour, water, yeast, and salt processed by mixing them into one dough then fermented and baked in the oven until cooked. Roti has several types, one of which is burger buns. Burger patties are white bread that is round or oval, made from high protein wheat flour, yeast, sugar, bread improver, salt, butter, milk powder, water, and usually with the addition of sesame seeds. The purpose of this study was to determine the formulation of burger patties high in dietary fiber and preferred by consumers. This study used a two-factor Complete Randomized Design (RAL), with a ratio of wheat flour and mocaf 70:30, 60:40, 50:50 with the addition of the percentage of beet tubers 30,40,50. The results of burger buns with high-fiber formulations were obtained from the ratio of wheat flour and mocaf flour at 50%:50% with a percentage of beet puree at 50%, this treatment has a fiber content of 11.47%, the water content of 26.10%, ash content 1.58%, fat content 4.33%, protein content 6.53%, carbohydrate content 61.45%, calories 310.89%, specific development volume 4.42%. Of flavor 3,38, color sensory test 3.73, chewiness 3.81, tenderness 3.11. Burger buns with raw materials of mocaf flour and the addition of beet puree as a source of fiber can be one of the practical foods that have good nutritional value for health.